Effects of Arginine Supplementation on Serum Metabolites and the Rumen Bacterial Community of Sika Deer (Cervus nippon) - Si, Huazhe; Liu, Hanlu; Nan, Weixiao; Li, Guangyu; Li, Zhipeng; Lou, Yujie (Frontiers in Veterinary Science, 2021)
Velvet antler is a regeneration organ of sika deer (Cervus nippon) and an important Chinese medicine, and nutrient metabolism affects its growth. Here, we investigated the effects of arginine supplementation on antler growth, serum biochemical indices, and the rumen bacterial community of sika deer during the antler growth period. Fifteen male sika deer (6 years old) were randomly assigned to three dietary groups, which were supplemented with 0 (n=5, CON), 2.5 (n=5, LArg), or 5.0 g/d (n=5, HArg) L-arginine. Arginine supplementation increased the velvet antler average daily gain (P>0.05). The IGF-1, ALT and AST concentrations in the serum of LArg sika deer were significantly higher than those in the serum of CON (P<0.05) and HArg deer (P<0.05). Among the three groups, the acetate, propionate, butyrate, isobutyrate, isovalerate and valerate molar concentrations in the rumen of LArg sika deer were higher than those in the rumen of CON (P<0.05) and HArg deer (P<0.05). The phyla Bacteroidetes, Firmicutes, and Proteobacteria were dominant in the rumen of sika deer among the three groups. Comparison of alpha diversities showed that the ACE and Chao1 indices significantly increased in the LArg and HArg groups compared with those in the CON group. PCoA and ANOSIM results showed that the bacterial community was significantly changed between the CON and LArg groups. Moreover, the relative abundances of Fibrobacter spp. and Prevotellaceae_UCG-003 increased, but those of Clostridium_sensu_stricto_1 and Corynebacterium_1 decreased in the LArg and HArg groups compared with those in the CON group. Additionally, the relative abundances of 19 OTUs were significantly different between the LArg and HArg groups. These results revealed that arginine supplementation affected the sika deer rumen bacterial community and serum biochemical indices.